Bioplastic Based on Taro Starch Modified Polyvinyl Alcohol and Eggshell (Starch-PVA-CT) with Degradability Study - Siti Qomariah; Intan Syahbanu; Puji Ardiningsih (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
Taro (Colocasia esculenta L. Schott) was potentially a raw material in the fabrication of bioplastic because of its biodegradability properties. Egg shells can be used as a filler in bioplastics because of their rich in calcium carbonate (CaCO3). This study aims to examine eggshell addition to starch-PVA-CT bioplastic properties. Taro tuber and eggshell were extracted first to obtain taro starch and calcium carbonate. Obtained products were incorporated with PVA, glycerol, and citric acid to produce bioplastics. Characteristic tests in this study included functional group analysis, hydrophilicity, mechanical properties, and degradation study in rivers. The taro starch obtained from this study was 4.8% from 900 g of taro tubers. Functional group analysis of bioplastics showed the presence of functional groups O-H, C-H, C-O ester, and C=O carbonyl. The hydrophilicity test showed the best percentage of water resistance in CL PVA/starch bioplastic (50% CT), and the decomposition in the river water environment reached 82%. The test results in this study showed that the best variation was in CL PVA/starch bioplastic (25% CT) with a tensile strength value of 2.05 Mpa and elongation at a break of 4%. These results meet the standards of SNI 7188.7:2016.